Global database of Andisols and associated meta-data from literature - Morimaru Kida; Rota Wagai (PANGAEA, 2025)
We synthesized a global Andisol database to improve estimates of global SOC stock and identify the key factors influencing spatial variation in SOC content in Andisols. Major samples (260 pedons, 1453 horizons) were obtained from the Tohoku University World Andosol Database (TUWAD) (Shoji et al., 1996; doi:10.1097/00010694-199609000-00005). All data in the TUWAD were manually checked by referring to the original publications, and any typographical errors, missing data in calculations, or incorrect placements of zeros where they should have been blanks, were corrected. Additional data were collected through a literature search in English on Web of Science. Our literature search was conducted for papers published from 1994 onwards post-compilation of TUWAD and was completed in November 2021. We excluded O and R horizons if they were reported (also from TUWAD), as we focused on mineral soil horizons. In total, we gathered 2854 samples from 574 pedons across 34 countries including data from TUWAD. Climatic variables included mean annual temperature (MAT) and mean annual precipitation minus potential evapotranspiration (MAP-PET), estimated by TerraClimate (data between 1958 and 2019, ~5 km resolution) (Abatzoglou et al., 2018; doi:10.1038/sdata.2017.191). Net primary production (NPP) data was estimated by MODIS/Terra Net Primary Production (MOD17A3HGF v006, data between 2000 and 2021, 500 m resolution) (Running & Zhao, 2021; doi:10.5067/modis/mod17a3hgf.061) and vegetation type was by Copernicus Global Land Cover Layers (CGLS-LC100 Collection 3, data between 2015 and 2019, 100 m resolution) (Buchhorn et al., 2020; doi:10.3390/rs12061044). For more specifications, please see the accompanying paper.